Brexanolone: An informative study - Rai, Sumit Kumar; Kuma, Keerthana; Deo, Shefali; Moudgil, Dr. Khayati (International Journal of Psychosocial Rehabilitation, 2020)
The birth of a baby will cause the joy, satisfaction, fear and anxiety to mix up with powerful emotions. Yet it may also lead to something that you do not foresee-depression. Upon childbirth most new mothers experience "baby blues," which usually include mood swings, crying kinds, anxiety, and sleeping difficulty. Usually, baby blues start within a two- to three-day span and can last up to two weeks. However, some new moms experience more serious, chronic depression called postpartum depression. Our aim is to include an Informative Overview of Brexanolone (Zulresso) in postpartum depression (PPD), a new antidepressant with a new mechanism of action.